Literature Review: Pengaruh Independensi, Skeptisme, dan Akuntabilitas Terhadap Kualitas Audit - Elsa Natali; Dea Maharani; Nera Marinda Machdar (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This literature review investigates the influence of independence, skepticism, and accountability on audit quality based on previous research. Independence is considered a key element in the audit process that can ensure the auditor's objectivity in conducting assessments. Skepticism, as the auditor's critical and alert attitude towards the information presented, is also considered important in improving audit quality. In addition, accountability refers to the auditor's responsibility in ensuring compliance with audit standards and professional ethics. Previous studies show that independence, skepticism, and accountability have a significant impact on audit quality. Auditors who have high independence tend to carry out more objective evaluations of the information being audited, thereby improving the quality of the financial reports produced. In addition, high skepticism allows auditors to be more alert to potential errors or fraud, thereby increasing their ability to detect discrepancies or irregularities in financial reports. Furthermore, strong accountability ensures that auditors are accountable for their decisions and actions, which can encourage them to conduct audits with high integrity and professionalism. Although many studies have confirmed the positive relationship between independence, skepticism, and accountability and audit quality, there is still room for further research in different contexts, such as specific industries or countries that have unique regulatory and cultural characteristics. The implication of this literature is the importance of strengthening these factors in audit practice in order to increase public trust in the financial reports presented.